PENGARUH MINYAK ATSIRI DAN EKSTRAK ETANOLIK BEBAS MINYAK ATSIRI DARI RIMPANG JAHE MERAH (Zingiber officinale Rosc. klon merah) TERHADAP EFEK APRODISIAKA PADA TIKUS JANTAN - Dipta Wana Anandita; Nurlaila Nurlaila; Suwijiyo Pramono (Faculty of Pharmacy, Universitas Gadjah Mada, 2012)
Nowadays, many young men experience sexual disfunction due to many factors. Red ginger is traditionally used to solve problems related to sexual disfunction. Oleoresin compound of red ginger has been reported to function as aphrodisiac. This research aims to compare aphrodisiac effect of essential oil and essential oil free extract in male rats. Red ginger essential oil was obtained by destilation while the red ginger free of essential oil was extracted using ethanol 70%. Rats were divided into five groups, administered by : etanolic extract suspension (140 mg/kg BM), essential oil emultion (15 μl/kg BM), pasak bumi extract suspension as positive control (500mg/kg BM), red ginger powder suspension as positive control (2,5 g/kg BM), and CMC Na 1% suspension as negative control. All rats were treated orally for 32 days. Parameters measured were introduction, climbing, and coitus frequency. The result showed that essential oil increased libido but its activity was lower than pasak bumi. Etanolic extract of red ginger and red ginger powder did not increase libido and sexual activity as compared with negative control.